Eksploitasi Kepiting Rajungan di Bawah Ukuran Minimal (Baby Crab) di Provinsi Kepulauan Bangka Belitung Ditinjau dari Undang-Undang Nomor 45 Tahun 2009 tentang Perikanan - Fhatira Riniar Risky; Toni Toni; Rio Armanda Agustian (Lembaga Yasin AlSys, 2025)
This study was motivated by the widespread exploitation of undersized blue swimming crabs, commonly referred to as baby crabs, for food and snacks in the Bangka Belitung Islands Province. This practice violates prevailing legal provisions, particularly Law Number 45 of 2009 on Fisheries and Minister of Marine Affairs and Fisheries Regulation Number 7 of 2024 concerning the Management of Lobster, Crab, and Blue Swimming Crab. The objective of this study is to analyze the legality of baby crab exploitation and evaluate the effectiveness of law enforcement in preventing such practices. The research employed an empirical juridical method with a statutory and descriptive approach. Data were collected through observations and interviews with business actors, local communities, and the Department of Marine Affairs and Fisheries, supported by literature review. The findings reveal that the exploitation of baby crabs constitutes a criminal offense under fisheries law, as it violates Article 100C of Law Number 45 of 2009 and the provisions of Ministerial Regulation Number 7 of 2024. However, weak law enforcement, low public awareness, and the limited effectiveness of persuasive measures by authorities have allowed the practice to persist. Therefore, intensive supervision, consistent enforcement of sanctions, and collaborative efforts among local governments, academics, and NGOs are needed to enhance legal literacy among coastal communities in support of sustainable fisheries resource management.